2018
DOI: 10.1007/s00204-018-2368-8
|View full text |Cite
|
Sign up to set email alerts
|

The role of roughage provision on the absorption and disposition of the mycotoxin deoxynivalenol and its acetylated derivatives in calves: from field observations to toxicokinetics

Abstract: A clinical case in Belgium demonstrated that feeding a feed concentrate containing considerable levels of deoxynivalenol (DON, 1.13 mg/kg feed) induced severe liver failure in 2-to 3-month-old beef calves. Symptoms disappeared by replacing the highly contaminated corn and by stimulating ruminal development via roughage administration. A multi-mycotoxin contamination was demonstrated in feed samples collected at 15 different veal farms in Belgium. DON was most prevalent, contaminating 80% of the roughage sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…In contrary, Seeling et al [41] reported no effect on feed intake on feeding approximately 3.4 mg DON per kg at a reference DM of 88% complete ration, similar to Winkler et al using 5 mg DON/kg feed showed no effect on performance parameters on dairy cattle [65]. In calves, Valgaeren et al [49] reported severe liver failure in 2-3 months old calves with no functioning rumen induced by 1.13 mg DON/kg feed, indicating the significance of rumen microbiota in DON degradation.…”
Section: Deoxynivalenolmentioning
confidence: 82%
See 2 more Smart Citations
“…In contrary, Seeling et al [41] reported no effect on feed intake on feeding approximately 3.4 mg DON per kg at a reference DM of 88% complete ration, similar to Winkler et al using 5 mg DON/kg feed showed no effect on performance parameters on dairy cattle [65]. In calves, Valgaeren et al [49] reported severe liver failure in 2-3 months old calves with no functioning rumen induced by 1.13 mg DON/kg feed, indicating the significance of rumen microbiota in DON degradation.…”
Section: Deoxynivalenolmentioning
confidence: 82%
“…The intact ruminal epithelium is an effective barrier against DON and ZEN [47]. DON is degraded by the ruminal microbiota to the less toxic metabolite de-epoxy DON (DOM-1) [48,49]. A study by Seeling et al [48] reported 94%-99% biotransformation of DON to DOM-1.…”
Section: Impact Of Mycotoxins In Dairymentioning
confidence: 99%
See 1 more Smart Citation
“…However, in high-productive dairy cows, mycotoxin-associated subclinical health problems may occur, reflected by vague and non-specific symptoms and periodic decrease in milk production [2]. One possible reason could be the higher proportion of maize silage in the ration of higher yielders [2], which is more vulnerable to contamination with multiple mycotoxins than e.g., grassland products [12][13][14]. However, in Belgium and the Netherlands, maize silage is also given to non-lactating cows instead of grassland products as maize silage is low in calcium and potassium which diminish the incidence of milk fever at the beginning of lactation [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…DON‐3‐GlcA was the major metabolite of DON and acetylated forms. Scarce DON‐15‐GlcA was found in urine (Valgaeren et al., 2019). Another study conducted both in vivo (in human liver, small intestine, and kidney) and in vitro (in HepG2 cells, Caco‐2 cells, and T84 cells) confirmed complete deacetylation fate of 3‐ADON and 15‐ADON, and liver and small intestine were identified as the main site of deacetylation reaction in humans (Figure 2d).…”
Section: Toxicity Of Don and Its Modified Formsmentioning
confidence: 99%